Pengembangan Media Video Animasi pada Materi Kecepatan Jarak dan Waktu Kelas V di Sekolah Dasar - Gusma Dewi; Zaka Hadikusuma Ramadan (Journal of Elementary School (JOES), 2021)
This research aims to develop learning media in the form of animated videos that are appropriate for learning mathematics on the subject of speed, distance and time for fifth grade elementary school. This learning media is expected to attract the attention of students to participate in the learning process and strengthen students' knowledge about speed, distance and time. The method in this study uses development research with the ADDIE model. This research uses three stages. (1) the analysis phase, namely the analysis of the material, educators and students, (2) the design phase, which is to design a product that has been determined by selecting the software that will be used to create the media, (3) the development phase, which is to test validity. The results of this study indicate that the expert's assessment of animated video media is categorized as very valid with a percentage of 95%. Then the material expert's assessment of the animated video media is categorized as very valid with a percentage of 86.25%. Furthermore, the linguist's assessment of the animated video media is categorized as very valid with a percentage of 85%. Overall, the validation results from media experts, material experts, and linguists obtained an average of 88.75% with very valid criteria. Keywords: Development, Video Media, Mathematics